2019
DOI: 10.1093/aobpla/plz004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased precipitation on the life history of spring- and autumn-germinated plants of the cold desert annual Erodium oxyrhynchum (Geraniaceae)

Abstract: Future increased precipitation in cold desert ecosystems may impact annual/ephemeral plant species that germinate in both spring and autumn. Our primary aim was to compare the life history characteristics of plants from spring-germinating (SG) and autumn-germinating (AG) seeds of Erodium oxyrhynchum. Plants in field plots with simulated increases in precipitation of 0, 30 and 50 % in spring and summer were monitored to determine seedling survival, phenology, plant size, seed production and biomass accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 46 publications
(57 reference statements)
2
21
0
1
Order By: Relevance
“…Similarly, some water manipulation experiments in arid and semiarid ecosystems showed that reductions in the amount of rainfall usually limit plant growth and/or seed production, whereas an increased water supply has the opposite effect (Breen & Richards, 2008; Volis, Ormanbekova & Yermekbayev, 2015; Mojzes et al, 2018). The response of E. gmelinii root/shoot ratio to rainfall amount was consistent with that of plants growing in arid regions, in which increased allocation to roots may be advantageous for capturing limiting soil resources (Padilla et al, 2013; Gao et al, 2015; Shan et al, 2018; Chen et al, 2019a). Moreover, under high amounts of rainfall (150% and 125%), plant growth and reproductive traits under the rainfall frequency of 10-day interval were significantly higher than those observed in association with other frequencies (Figs.…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, some water manipulation experiments in arid and semiarid ecosystems showed that reductions in the amount of rainfall usually limit plant growth and/or seed production, whereas an increased water supply has the opposite effect (Breen & Richards, 2008; Volis, Ormanbekova & Yermekbayev, 2015; Mojzes et al, 2018). The response of E. gmelinii root/shoot ratio to rainfall amount was consistent with that of plants growing in arid regions, in which increased allocation to roots may be advantageous for capturing limiting soil resources (Padilla et al, 2013; Gao et al, 2015; Shan et al, 2018; Chen et al, 2019a). Moreover, under high amounts of rainfall (150% and 125%), plant growth and reproductive traits under the rainfall frequency of 10-day interval were significantly higher than those observed in association with other frequencies (Figs.…”
Section: Discussionsupporting
confidence: 70%
“…Thus, by early spring of the next year when the soil is wet due to snow melt and low soil temperatures are suitable for germination, seeds can germinate rapidly and to high percentages. These patterns were also reported in other cold desert species such as Eremopyrum distans (Wang et al, 2010a), Isatis violascens (Zhou et al, 2015) and Erodium oxyrhynchum (Chen et al, 2019a,b). By late March of the next year, seedlings emerge and grow rapidly when soil temperatures start rising again, and rain is available.…”
Section: Discussionsupporting
confidence: 68%
“…Although herbaceous perennials are an important component of the cold desert vegetation of Central Asia (Tang et al, 2009; Sharma and Sharma; 2010; Baskin and Baskin, 2014), their seed germination ecophysiology has received relatively little research attention (Tang et al, 2009; Fu et al, 2013; Mamut et al, 2014b). On the other hand, much research has been done on the germination of cold desert annuals of Central Asia (Sun et al, 2009; Lu et al, 2010, 2015; Ma et al, 2010; Tang et al, 2010; Wang et al, 2010a; Mamut et al, 2014a; Zhou et al, 2015; Chen et al, 2019a,b). For various species of annuals, rainfall in autumn promotes the germination of some seeds in a given cohort (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, some water manipulation experiments in arid and semiarid ecosystems showed that reductions in the amount of rainfall usually limit plant growth and/or seed production, whereas an increased water supply has the opposite effect (Breen and Richards 2008, Volis et al 2015, Mojzes et al 2018. The response of E. gmelinii root/shoot ratio to rainfall amount was consistent with that of plants growing in arid regions, in which increased allocation to roots may be advantageous for capturing limiting soil resources (Padilla et al 2013, Gao et al 2015, Shan et al 2018, Chen et al 2019a. Moreover, under high amounts of rainfall (150% and 125%), plant growth and reproductive traits under the rainfall frequency of 10-day interval were significantly higher than those observed in association with other frequencies (Fig.…”
Section: Discussionmentioning
confidence: 55%